Attentional Control in Adolescent Mice Assessed with a Modified Five Choice Serial Reaction Time Task - Ciampoli, Mariasole (Sci Rep, 2017)
Adolescence is a critical period for the development of higher-order cognitive functions. Unlike in humans, very limited tools are available to assess such cognitive abilities in adolescent rodents. We implemented a modified 5-Choice Serial Reaction Time Task (5CSRTT) to selectively measure attentiveness, impulsivity, broad monitoring, processing speed and distractibility in adolescent mice. 21-day old C57BL/6J mice reliably acquired this task with no sex-dependent differences in 10–12 days. A protocol previously used in adults was less effective to assess impulsiveness in adolescents, but revealed increased vulnerability in females. Next, we distinctively assessed selective, divided and broad monitoring attention modeling the human Spatial Attentional Resource Allocation Task (SARAT). Finally, we measured susceptibility to distractions using non-predictive cues that selectively disrupted attention. These paradigms were also applied to two genetically modified lines: the dopamine transporter (DAT) and catechol-O-methyltransferase (COMT) heterozygous. Adolescent DAT hypo-functioning mice showed attentional deficits and higher impulsivity as found in adults. In contrast to adults, adolescent COMT hypo-functioning mice showed decreased impulsivity and attentional resilience to distractors. These paradigms open new avenues to study the establishment of higher-order cognitive functions in mice, as well as an effective tool for drug-testing and genetic screenings focused on adolescence.